2008
DOI: 10.1021/ie8009582
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation into the Production Behavior of Methane Hydrate in Porous Sediment with Hot Brine Stimulation

Abstract: The gas production behavior from methane hydrate in porous sediment by injecting the brine with the salinity of 0-24 wt % and the temperature of -1 to 130 °C was investigated in a one-dimensional experimental apparatus. The results show that the gas production process consists of three periods: the free gas production, the hydrate dissociation, and the general gas reservoir production. The hydrate dissociation accompanies the temperature decrease with the injection of the brine (NaCl solution), and the dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 15 publications
(32 reference statements)
3
80
0
1
Order By: Relevance
“…The differences among the three cases appear as the injection process starts. Figure 4 shows that the higher the salinity of the injected brine is, the faster the Q PT and Q R become, which is in good agreement with the experimental investigation by Li et al [10].…”
Section: Sensitivity To the Salinity Of The Injected Watersupporting
confidence: 89%
See 1 more Smart Citation
“…The differences among the three cases appear as the injection process starts. Figure 4 shows that the higher the salinity of the injected brine is, the faster the Q PT and Q R become, which is in good agreement with the experimental investigation by Li et al [10].…”
Section: Sensitivity To the Salinity Of The Injected Watersupporting
confidence: 89%
“…Li et al [9] indicated that the hot brine stimulation experiment could obtain a higher energy efficiency than that using hot water stimulation. Subsequently, Li et al [10] further indicated that the hydrate dissociation rate increased with the increase of salinity. Recently, Moridis et al [11] showed that the dual horizontal well system is better than the single horizontal well layout because of preferable heat transference.…”
Section: Introductionmentioning
confidence: 97%
“…The common methods for hydrate dissociation are: (1) the depressurization method, in which the hydrate reservoir pressure is reduced below the equilibrium decomposition pressure to decompose the hydrate [37,38]; (2) the thermal stimulation method, in which the hydrate reservoirs are heated above the equilibrium decomposition temperature to decompose the hydrate [21,39]; (3) the chemical injection method, in which chemicals (such as methanol or ethylene glycol) are injected into the reservoir to change the equilibrium hydrate decomposition conditions and induce hydrate dissociation [40,41]; and (4) the CO 2 replacement method, in which CO 2 is injected into the hydrate reservoirs to replace the methane gas [42,43]. A series of field production tests from the practical hydrate reservoirs have confirmed the availability of these methods, such as the test at the Mackenzie Delta (Northwest Territories, Canada) by thermal stimulation and depressurization methods [19], and the offshore test at the Nankai Trough, Japan by the depressurization method during 12-18 March 2013 [44].…”
Section: Methods Of Production and Well Designmentioning
confidence: 99%
“…The attractiveness of gas hydrates as a potential future energy source is increasing on account of the abundance of the resource and the growing global energy demands. There are four main methods for exploiting hydrate from hydrate accumulations: depressurization [3][4][5][6][7], thermal stimulation [8][9][10][11][12][13], inhibitor stimulation [14][15][16][17], and carbon dioxide replacement [18,19]. The depressurization method has received considerable attention for hydrate dissociation because of its easy operation and high energy efficiency.…”
Section: Introductionmentioning
confidence: 99%